ANÁLISIS METODOLÓGICO DE PROGRAMAS “CALL” - Sánchez Ortega, Andrés (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract In an attempt to keep pace with new technology in all aspects of today’s life, we undertook the study of the recent Second Language Acquisition methodological tendency brought about by the use of computers in the language classroom (or at the student’s home). The objective of the work is to develop a questionnaire based on the most outstanding and most generally accepted theories and principles through which one can arrive at the acquisition of the L2 (i.e. input, output, interaction, motivation, error analysis, pedagogical principles, communicative competence). Once we developed the questionnaire, we applied it to CALL programmes through a thorough analysis of their operation. We then will have an objective test of the degree of methodological principles observed in the computer programmes. One conclusion of the research is that this new teaching methodology aide is beginning to attract the attention of the students and educators alike. CALL applications can assume brilliantly the role of the book and improve upon it. We make it clear that, in addition to the linguistic and technological views, the methodological view is one of the components that must be taken into account when making a CALL programme.